Social Characterization of Speech (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
Sociolinguistics is a comprehensive analysis of speech. Social analysis of speech allows for a broader analysis of the place of language in our society. As a result of gender linguistics, different aspects of female and male speech are being studied. By revealing the age-specific characteristics of speech, the differences in the speech of teenagers and the elderly were considered.